Gallup Democracy in Exercising the NATO Membership Option: The Cases of Finland and Sweden - Vesa Kanniainen (Center for Economic Studies and ifo Institute (CESifo), 2022)
The paper asks whether the exercising of the NATO membership option is justified for Finland and Sweden in the light of their geopolitical state after Russia's attack on Ukraine. It was the Gallup democracy, which launched the political moves towards the membership. In both countries, the majority of people turned to favor the membership within 2-3 months. Finland activated first. Sweden was fast in catching up with the Finnish process. The theory of option pricing is employed to analyze the optimal timing of exercising the option when the uncertainty regarding the value of the membership is rapidly diluting. The Turkish intervention in the membership process after the membership applications of Finland and Sweden were delivered suggests a bargaining phase once the application is delivered. Finally, the effects of the Gallup surveys on the political equilibrium are analyzed in a voter-politician model.
Keywords: D72; D74; H56; 330; Gallup democracy; defense alliance; option value of membership